1998
DOI: 10.1097/00005392-199808000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Melanotropic Peptide Initiates Erections in Men With Psychogenic Erectile Dysfunction

Abstract: Melanotan-II is a potent initiator of erections in men with psychogenic erectile dysfunction and has manageable side effects at a dose of 0.025 mg./kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While this study did not measure the ability of the men to perform sexual intercourse, the quality of rigidity at >60% has some correlation with the ability to perform intercourse. The Rigiscan™ device is used for the pharmacodynamic evaluation of investigational treatments of ED [9, 10, 11]. However, Rigiscan™ measurements evaluate only a limited aspect of overall sexual performance and the data from pharmacodynamic observations like the present need to be confirmed by further real–life pharmacotherapeutic observations [12].…”
Section: Discussionmentioning
confidence: 99%
“…While this study did not measure the ability of the men to perform sexual intercourse, the quality of rigidity at >60% has some correlation with the ability to perform intercourse. The Rigiscan™ device is used for the pharmacodynamic evaluation of investigational treatments of ED [9, 10, 11]. However, Rigiscan™ measurements evaluate only a limited aspect of overall sexual performance and the data from pharmacodynamic observations like the present need to be confirmed by further real–life pharmacotherapeutic observations [12].…”
Section: Discussionmentioning
confidence: 99%
“…. This compound has been used very extensively worldwide to study melanotropin biological activity, and also has been in clinical trials for erectile dysfunction …”
Section: Linear To Cyclic Analogsmentioning
confidence: 99%
“…Among other findings, we demonstrated that MT‐I (and later MT‐II) led to pigmentation throughout the body without sun and that this hormone‐induced pigment could reduce UV radiation‐induced DNA damage in humans. Equally exciting was the finding that MT‐II, in a double blind, placebo controlled, clinical trial could lead to erectile function in men with non‐organic erectile dysfunction when given peripherally. These compounds may soon be in clinical medicine.…”
Section: Resultsmentioning
confidence: 99%